Pengaruh Metode Pembelajaran Active Knowledge Sharing Terhadap Hasil Belajar Sejarah Siswa Kelas XI - Joni Pranata; Muhammad Basri; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this research is to analyze and determine whether there is a significant influence on learning outcomes in history subjects through the application of Active Knowledge Sharing learning methods for students of eleventh grade social students at Ma'arif NU 05 Purbolinggo High School. This research uses the One Shot Case Study method. Statistical data analysis technique uses a simple linear regression formula. The results of this study and discussion concluded that the working hypothesis (H1) was accepted, namely